The compromise of liberal environmentalism - Bernstein, Steven (Columbia Univ. Press, 2001)
A significant shift in environmental governance since 1970 has been the convergence of environmental and liberal economic norms towards liberal environmentalism. This text assesses the reasons for this shift, and considers the implications.
Keywords: Nachhaltigkeit; Umweltpolitik; Environmental policy; Sustainable development; Liberalismus